Evaluation of Natural Peptides to Prevent and Reduce the Novel SARS-CoV-2 Infection - María Paredes-Ramos; Enma Conde Piñeiro; Horacio Pérez-Sánchez; José M. López-Vilariño (Journal of Food Quality)
In a preventive context, natural peptides can play a major role against SARS-CoV-2, so their character of GRAS (generally recognized as safe) means they would not need innocuity analyses to be employed. This study analyses the potential of pea peptides, LSDRFS and SDRFSY, and amaranth peptides, GGV, IGV, IVG, VGVL, and VIKP, against the SARS-CoV-2 hosts, ACE2 (angiotensin-converting enzyme 2), ACE (angiotensin-converting enzyme), and CD26 (cluster of differentiation 26), and SARS-CoV-2 enzymes, spike glycoprotein and 3CLpro (3-chymotrypsin-like protease). Also, currently used drugs were analysed to contrast drug and peptide behaviour. Employing docking, virtual screening, and molecular dynamics assays, SDRFSY, LSDRFS, and VIKP were detected as potential bioactive peptides by blocking ACE2 and CD26 or reducing the inflammation associated with COVID-19. Enzyme inhibition analyses were also performed, proving the ability of SDRFSY and LSDRFS as ACE2-blocking agents against the spike glycoprotein with inhibition capacities above 80%.